STRATEGI SISTEM INFORMASI MANAJEMEN PRESENSI KARYAWAN (FINGER) TERHADAP PENYESUAIAN MEJA KERJA WORKSHOP (STACKING DIVITION) DI PT. SCHNEIDER INDONESIA - Sutomo .; Nelson Pardede; Erna Erna Indriastiningsih (Universitas Sahid Surakarta, 2015)
Management information systems if designed and implemented well, there will be many benefits that can be obtained by the company's management, which facilitatesmanagement and helps and supports the management decision-making process. The importance of the role of management information systems in efforts to achieve goals, so it is clear that the use of management information systems must be linked to modernization efforts, while the modernization process can only occur if the benefitsare drawn from the progress made in the fields of science and technology. Technology has developed so rapidly, so that product equipment products have become a staple in each of the inseparable jobs. in other words the development of technology is an important indication in improving products in various types of work. Workers can reachwork equipment according to the position of work time and according to the size of the anthropometry. Anthropometry and its application in designing work facilitiesAnthropometry will be widely used as ergonomic considerations in requiring human interaction. correct guidance and instruction, as well as training on the introduction ofequipment and workplaces on a regular basis, so as to make a habit of positive work ingrained (habit), the most important problem is the occurrence of fatigue, which canoccur that ergonomic problems can resulting in accelerating the occurrence of fatigue in the workplace.